Job Displacement and Local Employment Density - David C. Maré; Richard Fabling; Dean Hyslop (Institute of Labor Economics (IZA), 2023)
Past research finds evidence that workers' labour market outcomes are enhanced if they live in areas with greater job opportunities and employment density. Using two alternative measures of the employment density and job opportunities faced by workers in the local labour market in which they were displaced, this paper analyses their effects on the subsequent migration decisions and labour market outcomes of workers who involuntarily lose their jobs as part of a firm closure or mass layoff event. Our analysis finds only limited support for the spatial mismatch hypothesis. The results imply that workers displaced from jobs in areas with greater employment density or job opportunities are more likely to emigrate, are less likely to be re-employed following layoff and have lower subsequent earnings, although earnings are higher conditional on being employed. However, if employed, workers displaced in areas with more opportunities are less likely to have moved area, but more likely to have changed industry, and have a more similar job to that from which they were displaced.
Keywords: J62; J64; R23; 330; displaced workers; unemployment duration; local labour markets